A randomized controlled clinical trial of carbohydrate mix-fortified nutrition in type 2 diabetes mellitus patients (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Liquid meal replacement nutrition (LMRN) contains low glycemic index food (isomaltulose, resistant dextrin, and inulin), which can decrease large blood glucose level fluctuations and reduce food intake. This study aimed to determine the stability of daily blood glucose and the level of appetite sensations after intake of LMRN in type 2 diabetes mellitus (DM) patients. METHODS This randomized, controlled, crossover, and open-labeled study included 30 subjects with type 2 DM. Subjects attended two visit sessions to consume either LMRN or controlled-nutrition solid food (CNSF) for 4 consecutive days. Each subject had 2 days of 24-hour periods of blood glucose measurement using a continuous glucose monitoring system and had a 1-week washout period. Glycemic response (GR) and incremental area under the curve (iAUC) were calculated. The satiety level was measured using a visual analog scale. RESULTS After 48 hours, LMRN reduced GR compared with CNSF with glucose measurements of 13.72 (30.42) and 17.47 (36.38) mg/dl, respectively. The reduction on iAUC after consuming LMRN (36,891 [30,255.8] mg.min/dl) compared with CNSF (40,641 [38,798.9] mg.min/dl) was also noted. Subjects having LMRN felt less hungry and more satiated than those consuming CNSF. The administration of LMRN does not have any serious side effects. CONCLUSIONS LMRN provides a greater reduction of GR and longer term of satiety compared with CNSF without causing any serious side effects.